Tales from the Canadian Crypt:: Canadian Ghosts, the Cultural Uncanny, and the Necessity of Haunting in Ann-Marie MacDonald’s Fall on Your Knees - Baetz, Joel (Studies in Canadian Literature / Études en littérature canadienne, 2004)
From Earl Birney to Northrop Frye to Tomson Highway , Canadian writers have contributed to the notion of Canada as a blank space, and have created a literary tradition rooted in notions of Canadian cultural absence. The motif of haunting in Ann-Marie MacDonald's Fall on Your Knees works to challenge both the limits of official history and the notion of impermeable identity. Relying on Freud's concept of the uncanny as the intersection of the strange with the familiar, MacDonald constructs a narrative in which both identities and geographies are subject to rnegotiation. MacDonald's characters continually renegotiate their individual and cultural identities, and her narrative stages a redemption of the uncanny history of Cape Breton.